Lattice distortion in hcp rare gas solids - Grechnev, A.; Tretyak, S.M.; Freiman, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The lattice distortion parameter δ ≡ c/a – Ö8̅/̅3̅ has been calculated as a function of molar volume for the hcpphases of He, Ar, Kr, and Xe. Results from both semi-empirical potentials and density functional theory are presented. Our study shows that δ is negative for helium in the entire pressure range. For Ar, Kr, and Xe, however, δ changes sign from negative to positive as the pressure increases, growing rapidly in magnitude at higher pressures.